The Darkside of Artificial Intelligence to Consumer Behavior: Bibliometric Review - Qanita Putri Muslik, Sintara; Mulia Wibawa, Berto; Windharto, Agus (Journal of Accounting and Finance Management, 2025)
Artificial Intelligence (AI) is a technology that continues to be developed today. Providing a positive impact on life in facilitating human work, unfortunately AI also has a bad side that causes anxiety. The purpose of this research is to explain the negative impacts associated with AI in the world of business management. This research is expected to provide an understanding of the dark side of AI on consumer behavior and its implications through a systematic literature review and in-depth content analysis. The data used in this study were taken from Scopus and Web of Science using bibliometric methods. Using the help of RStudio and biblioshiny applications to manage data. The results showed that there is a significant correlation between the negative impact of Artificial Intelligence (AI) on consumer behavior, where the negative impact of AI significantly affects consumer behavior. This study provides important new knowledge for researchers and the public who seek information about the relationship between the negative impact of AI and consumer behavior.